2007
DOI: 10.1111/j.1748-8583.2007.00059.x
|View full text |Cite
|
Sign up to set email alerts
|

HR practices and commitment to change: an employee‐level analysis

Abstract: This article explores the relationship between HR practices and commitment to change in three health service organisations in Ireland. The research focuses on employee views of HR practices and resulting employee‐level consequences including commitment to change, perceptions of the industrial relations climate and the psychological contract, and work–life balance. The findings indicate that the HR practices valued by employees, and which are related to a range of employee‐related consequences, are very differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
0
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(139 citation statements)
references
References 36 publications
3
123
0
10
Order By: Relevance
“…Individual differences in the perceptions of and reactions to an organisation's HRM practices stem from a range of factors such as past experience, values and beliefs or individual expectations (Den Hartog, Boselie and Paauwe, 2004). Hence, the same HRM system can be interpreted in different or even contrary ways, and it is individuals' perceptions of this system that are most relevant to individual level attitudinal and behavioural outcomes (Guest, 1999, Gerhart, Wright, McMahan and Snell, 2000, Gratton and Truss, 2003, Gerhart, 2005, Conway and Monks, 2008, Kuvaas, 2008. Whilst a wide range of studies have examined how single HRM practices such as selection, training or performance management influence individual level behaviours (for an overview see Boswell, 2002, Boselie, Dietz andBoon, 2005), more recently researchers have argued that HRM practices and strategies need to be considered holistically rather than as individual practices to assess their impact on employee outcomes Mohamed, 2010, Snape andRedman, 2010).…”
Section: The Impact Of Perceived Hrm Practices On Ocb and Turnover Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual differences in the perceptions of and reactions to an organisation's HRM practices stem from a range of factors such as past experience, values and beliefs or individual expectations (Den Hartog, Boselie and Paauwe, 2004). Hence, the same HRM system can be interpreted in different or even contrary ways, and it is individuals' perceptions of this system that are most relevant to individual level attitudinal and behavioural outcomes (Guest, 1999, Gerhart, Wright, McMahan and Snell, 2000, Gratton and Truss, 2003, Gerhart, 2005, Conway and Monks, 2008, Kuvaas, 2008. Whilst a wide range of studies have examined how single HRM practices such as selection, training or performance management influence individual level behaviours (for an overview see Boswell, 2002, Boselie, Dietz andBoon, 2005), more recently researchers have argued that HRM practices and strategies need to be considered holistically rather than as individual practices to assess their impact on employee outcomes Mohamed, 2010, Snape andRedman, 2010).…”
Section: The Impact Of Perceived Hrm Practices On Ocb and Turnover Inmentioning
confidence: 99%
“…We cannot assume that simply capturing policy data on an organisation's HRM strategy is sufficient to shed light on employees' experiences or beliefs about HRM (Gratton and Truss, 2003, Conway and Monks, 2008, Snape and Redman, 2010. As Nishii et al (2008) observed, individual perceptions of the aims and impact of HRM policies and practices inevitably vary.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is much more interesting to get a grasp on the role that the employee's perception of the training plays than to count the number of employees trained or the number of training programs introduced. It is indeed difficult to assume that merely increasing investment and programs for learning will suffice to produce results [20][21][22], without taking into account the reaction of the employee to these programs. In the same vein, the organization cannot expect a return on its investment in training until the transfer of learning has been tangibly felt in employees' daily work.…”
Section: Introductionmentioning
confidence: 99%
“…It's management responsibility to be honest and supportive to practices two-way communication systems (Lee et al 2010) as well as informed the rules, regulations, standard and organizational results to the employees which also provide the openness of managerial practices (Conway et al 2008). Empirical studies by Liu et al (2007) have proven that communication and information sharing has direct positive correlations with affective commitment.…”
Section: Communication and Information Sharingmentioning
confidence: 99%